An overview on plasma-assisted thermochemical treatments of martensitic stainless steels - Scheuer, Cristiano José; Cardoso, Rodrigo Perito; Brunatto, Silvio Francisco (Surface topography metrology and properties, 2023)
Demand for higher wear and corrosion resistance components has attracted increasing interest in surface engineering. This line of research develops alternative processes for improving the surface properties of engineering materials. The traditional route seeks the development of new alloys. However, the cost and time associated with these developments become prohibitive in many cases. Currently, the application of plasma-assisted thermochemical treatments has been a technically and economically viable alternative to extend the lifespan of components exposed to severe environments. In this sense, the tooling industry is one of the oldest and most traditional users of plasma-assisted processes, since forming, injection and/or cutting tools are usually subjected to wear and corrosion degradation. Among the various materials used to make tools, we highlight the martensitic stainless steels, which are used in the manufacture of molds and inserts for injection of chlorinated and fluorinated thermoplastic and thermoset polymers. In these applications, martensitic stainless steels are exposed to severe deterioration conditions due to abrasive wear and corrosion by chloride and fluoride ions. Considering the variety of available plasma-assisted thermochemical treatments whose application allows improving metallic materials corrosion and wear resistance, it is a complex task to select the better process and its execution parameters to ensure the maximum performance in operation. In this work, it is proposed a systematic method to aid the process selection task, focused on thermochemical treatments of martensitic stainless steels, which integrates the processing conditions and the resulting microstructure, properties and performance. For this purpose, working envelop for selecting processes and processing parameters were elaborated, that allow qualify and quantify the correlations among each specific plasma-assisted thermochemical treatment (like nitriding, carburizing, nitrocarburizing, etc.) execution conditions, with the resulting properties and performance for treated martensitic stainless steels. In parallel, the genesis of plasma-assisted thermochemical treatments is also described, a bibliometric analysis is carried out on the publications on the subject, and also, a summary description of the surface characteristics of the treated materials is realized.